Spinel high-entropy oxide material and preparation method and application thereof

CN122977455APending Publication Date: 2026-10-27SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610626786.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-08
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]鉴于上述现有技术的不足,本发明的目的在于提供一种尖晶石高熵氧化物材料及其制备方法与应用,旨在解决现有高熵氧化物的制备方法存在元素混合不均,且转化效率低的问题

Benefits of technology

[0005]鉴于上述现有技术的不足,本发明的目的在于提供一种尖晶石高熵氧化物材料及其制备方法与应用,旨在解决现有高熵氧化物的制备方法存在元素混合不均,且转化效率低的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977455A_ABST
    Figure CN122977455A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of nanomaterials, in particular to a spinel high-entropy oxide material and a preparation method and application thereof, the preparation method comprising the following steps: mixing iron salt, cobalt salt, nickel salt, manganese salt and copper salt with a solvent, carrying out stirring treatment and ultrasonic treatment, carrying out freeze-drying treatment on the obtained mixed solution, placing the obtained multi-metal salt precursor in an inductively coupled plasma reaction device, carrying out cooling after plasma reaction, and obtaining the spinel high-entropy oxide material. The inductively coupled plasma reaction device is used to generate a high-temperature plasma jet containing high-activity particles through the inductive coupling of a high-frequency electromagnetic field and working gas, so that the plasma acts on the multi-metal salt precursor, and the multi-metal salt precursor simultaneously experiences instantaneous pyrolysis oxidation, synchronous dehydration and rapid quenching in millisecond-level time, thereby realizing the uniform mixing of metal elements at the atomic level, and finally forming a high-entropy oxide with a single-phase crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterials technology, and in particular to a spinel high-entropy oxide material, its preparation method, and its application. Background Technology

[0002] High-entropy oxides (HEOs) are multi-element oxide materials composed of five or more metal elements in equimolar or near-equimolar proportions, forming a single crystal structure. Benefiting from their unique "four major effects"—the thermodynamic high-entropy effect, the structural lattice distortion effect, the kinetic hysteresis diffusion effect, and the performance "cocktail" effect—HEOs show broad application prospects in electrocatalysis, energy storage, high-temperature protection, and structural materials. Especially in electrocatalysis fields such as the oxygen evolution reaction (OER), HEOs, with their multi-element synergistic effect, tunable electronic structure, and excellent structural stability, are considered important candidate materials to replace noble metal catalysts. However, the synthesis of HEOs faces challenges such as achieving a uniform mixing of multiple metal elements at the atomic scale to form a single crystalline phase, while avoiding elemental segregation, multiphase separation, and grain coarsening.

[0003] Currently, common methods for synthesizing high-entropy oxides include traditional solid-state reaction methods, wet chemical methods, plasma synthesis, and rapid synthesis methods such as laser scanning ablation and Joule heating. However, existing methods for synthesizing high-entropy oxides still have significant shortcomings in terms of uniform element mixing, microstructure control, process simplification, energy consumption control, and scalability.

[0004] Therefore, existing technologies still need to be improved and developed. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a spinel high-entropy oxide material, its preparation method and application, in order to solve the problems of uneven element mixing and low conversion efficiency in the existing preparation methods of high-entropy oxides.

[0006] The technical solution of the present invention is as follows: A method for preparing a spinel high-entropy oxide material includes the following steps: Iron salts, cobalt salts, nickel salts, manganese salts, and copper salts are mixed with a solvent, and then subjected to stirring and ultrasonic treatment to obtain a mixed solution. The mixed solution was freeze-dried to obtain a multi-metal salt precursor; The polymetallic salt precursor was placed in an inductively coupled plasma reactor and cooled after plasma reaction to obtain spinel high-entropy oxide material.

[0007] The method for preparing the spinel high-entropy oxide material, wherein the iron salt is selected from one or more of ferric nitrate, ferric chloride, ferric sulfate, and ferric acetate; the cobalt salt is selected from one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate; the nickel salt is selected from one or more of nickel nitrate, nickel chloride, nickel sulfate, and nickel acetate; the manganese salt is selected from one or more of manganese nitrate, manganese chloride, manganese sulfate, and manganese acetate; and the copper salt is selected from one or more of copper nitrate, copper chloride, copper sulfate, and copper acetate.

[0008] The method for preparing the spinel high-entropy oxide material, wherein the metal elements in the iron salt, cobalt salt, nickel salt, manganese salt and copper salt are in equal molar ratios.

[0009] The method for preparing the spinel high-entropy oxide material includes a stirring treatment time of 0.5h-2h; an ultrasonic treatment time of 0.5h-2h; and a freeze-drying treatment time of 24h-48h.

[0010] In the preparation method of the spinel high-entropy oxide material, the distance between the plasma torch inlet of the inductively coupled plasma reactor and the polymetallic salt precursor is 5mm-12mm.

[0011] The method for preparing the spinel high-entropy oxide material, wherein the plasma reaction power is 500W-1000W and the plasma reaction time is 3min-8min; Preferably, during the plasma reaction, the surface temperature of the polymetallic salt precursor is 800℃-1200℃.

[0012] The method for preparing the spinel high-entropy oxide material, wherein the working gas for the plasma reaction is a mixture of argon and oxygen; the flow rate of the argon is 1.0 slm-2.0 slm, and the flow rate of the oxygen is 30 sccm-100 sccm; Preferably, the cooling process involves introducing cooling gas.

[0013] A spinel high-entropy oxide material is prepared using the same preparation method as the spinel high-entropy oxide material.

[0014] The spinel high-entropy oxide material has a particle size of 200nm-450nm.

[0015] Application of a spinel high-entropy oxide material in water electrolysis catalyst.

[0016] Beneficial Effects: This invention provides a spinel high-entropy oxide material, its preparation method, and its application. The preparation method of the spinel high-entropy oxide material includes the following steps: mixing iron salt, cobalt salt, nickel salt, manganese salt, and copper salt with a solvent, followed by stirring and ultrasonic treatment to obtain a mixed solution; freeze-drying the mixed solution to obtain a multi-metal salt precursor; placing the multi-metal salt precursor in an inductively coupled plasma reactor, undergoing plasma reaction, and then cooling to obtain the spinel high-entropy oxide material. This invention utilizes a solution mixing method to sequentially stir, ultrasonically treat, and freeze-dry iron salt, cobalt salt, nickel salt, manganese salt, and copper salt in a solvent environment to obtain a multi-metal salt precursor. Then, using an inductively coupled plasma reactor, a high-temperature plasma jet containing highly active particles is generated through inductive coupling between a high-frequency electromagnetic field and a working gas. When the plasma acts on the multi-metal salt precursor, it simultaneously undergoes instantaneous pyrolysis oxidation, synchronous dehydration, and rapid quenching within milliseconds, thereby achieving uniform mixing of the various metal elements at the atomic level, ultimately forming a high-entropy oxide with a single-phase crystal structure. Meanwhile, this method can be used to prepare high-entropy oxides with atomic-level uniform mixing of multiple metals, controllable product microstructure, simple process, low energy consumption, and scale-up potential. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the process flow for preparing a spinel high-entropy oxide material according to the present invention; Figure 2 The X-ray diffraction pattern of the spinel high-entropy oxide material prepared in Example 1; Figure 3 This is a TEM image of the spinel high-entropy oxide material prepared in Example 1; Figure 4 This is a TEM-EDS elemental distribution diagram of the spinel high-entropy oxide material prepared in Example 1; Figure 5 The image shows the electrochemical performance characterization of the spinel high-entropy oxide material prepared in Example 1 as a catalyst in water electrolysis. Detailed Implementation

[0018] This invention provides a spinel high-entropy oxide material, its preparation method, and its applications. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0019] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined as herein.

[0020] Currently, the main problems with the synthesis methods of high-entropy oxides are as follows: 1) Traditional solid-state reaction method Solid-state reaction is the earliest method used for the synthesis of high-entropy oxides. It usually involves mixing various metal oxides or carbonate powders mechanically by ball milling and then sintering them at high temperatures (usually above 1000℃) for a long time (several hours to tens of hours) to allow the elements to diffuse and form a single-phase structure. This method has obvious drawbacks: (1) Mechanical mixing is difficult to achieve atomic-level uniformity, which easily leads to local compositional inhomogeneity and the generation of impurity phases; (2) High-temperature and long-term sintering causes severe grain coarsening (usually at the micrometer level), resulting in a small specific surface area, which is not conducive to surface-sensitive applications such as catalysis; (3) Multiple grinding and sintering steps make the process cumbersome, energy-intensive, and time-consuming.

[0021] 2) Wet chemical method Wet chemical methods (such as coprecipitation, sol-gel, hydrothermal / solvothermal methods, etc.) achieve element mixing at the molecular level by dissolving multiple metal salts in a solvent, followed by drying, calcination and other steps to convert them into high-entropy oxides. Compared with solid-phase methods, this method improves the uniformity of element mixing, but still has the following shortcomings: (1) The calcination process still requires a relatively high temperature (usually 600-900℃) and a relatively long time (several hours) to promote the formation of crystal phases, and there is still a risk of element segregation during this process; (2) The hydrolysis and precipitation rates of different metal ions vary greatly, making it difficult to accurately control the stoichiometric ratio; (3) The process involves multiple steps (precipitation, washing, drying, calcination), with a long cycle and poor batch stability.

[0022] 3) Rapid synthesis method In recent years, researchers have developed rapid synthesis strategies such as laser scanning ablation and Joule heating. Laser-assisted deposition (LAD) uses high-energy laser irradiation of the target material to effectively control oxygen vacancies, but this method has high equipment costs, extremely low yields, and is difficult to scale up for the preparation of powder materials. Ultrafast Joule heating utilizes electric current passing through a conductive carrier to generate instantaneous high temperatures (up to 2000K or higher) to achieve rapid reactions, but this method has stringent requirements for the conductivity of the precursor and carrier, difficulty in controlling the uniformity of the temperature field, and usually relies on conductive substrates such as carbon materials, which limits the purity and application range of the product.

[0023] 4) Existing plasma synthesis technology Plasma technology, with its high temperature, high activity, and rapid quenching characteristics, exhibits unique advantages in the synthesis of high-entropy oxides. However, existing plasma synthesis methods still face the following technical bottlenecks: i) Poor controllability of the microstructure of products synthesized by thermal plasma: Although DC arc or radio frequency thermal plasma (such as the 12 kW DC non-transfer arc thermal plasma reported by Amarnath et al.) can achieve rapid one-step synthesis of high-entropy oxides, the large temperature gradient of the plasma jet and the short reaction zone result in a wide particle size distribution (usually tens of nanometers to micrometers) and non-uniform morphology of the products. Furthermore, it imposes stringent requirements on the physical state of the precursor (such as powder particle size and flowability), making it difficult to achieve fine structural control. (AMARNATH P, MADHU R, PRAVEEN K, et al. Phase-pure high-entropy spineloxide (Ni, Fe, Mn, Cu, Zn)3O4 via thermal plasma: a promising electrocatalyst for oxygen evolution reaction[J]. ACS Applied Energy Materials, 2023, 6:5899-5911.) ii) The two-step plasma treatment process is complex: Some studies employ a two-step strategy of "wet chemical synthesis precursor + plasma post-treatment" (e.g., Gu et al. first synthesized high-entropy layered double hydroxides via a solvothermal method, and then oxidized them with low-temperature oxygen plasma). Although this can achieve a high specific surface area, the process is lengthy and involves multiple steps, failing to fully utilize the rapid and efficient advantages of one-step plasma synthesis. (GU K, WANG D, XIE C, et al. Defect‐rich high‐entropyoxide nanosheets for efficient 5‐hydroxymethylfurfural electrooxidation[J].Angewandte Chemie, 2021, 133: 20415-20420.) iii) Low reactor energy efficiency and difficulty in scale-up: Existing plasma reactors generally suffer from low energy efficiency, with some energy consumed in electrode cooling and cavity heat dissipation. Moreover, the reactor structures are mostly custom-designed in the laboratory, making it difficult to directly scale up to industrial scale. In addition, existing methods lack the ability to synergistically control the atomic-level uniform mixing of multi-element components and the precise regulation of the product microstructure during the synthesis process.

[0024] Therefore, existing methods for synthesizing high-entropy oxides still have significant shortcomings in terms of uniform element mixing, microstructure control, process simplification, energy consumption control, and scalability potential.

[0025] Based on this, such as Figure 1 As shown, the present invention provides a method for preparing a spinel high-entropy oxide material, comprising the following steps: Step S10: Mix iron salt, cobalt salt, nickel salt, manganese salt, and copper salt with a solvent, and after stirring and ultrasonic treatment, obtain a mixed solution; Step S20: The mixed solution is freeze-dried to obtain a multi-metal salt precursor; Step S30: The polymetallic salt precursor is placed in an inductively coupled plasma reaction device, and cooled after plasma reaction to obtain spinel high-entropy oxide material.

[0026] In this embodiment, iron, cobalt, nickel, manganese, and copper salts are sequentially subjected to stirring, ultrasonic treatment, and freeze-drying in a solvent environment using a solution mixing method to obtain a multi-metal salt precursor. Then, an inductively coupled plasma reactor is used to generate a high-temperature plasma jet containing highly reactive particles through inductive coupling between a high-frequency electromagnetic field and the working gas. When the plasma acts on the multi-metal salt precursor, it simultaneously undergoes instantaneous pyrolysis oxidation, synchronous dehydration, and rapid quenching within milliseconds, thereby achieving uniform mixing of the various metal elements at the atomic level, ultimately forming a high-entropy oxide with a single-phase crystal structure. Furthermore, this method enables the preparation of high-entropy oxides with atomic-level uniform mixing of multiple metals, controllable product microstructure, simple process, low energy consumption, and scale-up potential.

[0027] Specifically, when plasma acts on the particulate polymetallic salt precursor, three key processes occur simultaneously within milliseconds, including: 1) Instantaneous pyrolysis oxidation: The high temperature field of thousands of Kelvin and a large number of active oxygen species (such as oxygen atoms and excited oxygen atoms) cause iron salts, cobalt salts, nickel salts, manganese salts and copper salts to decompose and oxidize rapidly; 2) Simultaneous dehydration: The adsorbed water and crystal water in the polymetallic salt precursor are vaporized instantaneously, promoting heat transfer and reaction uniformity; 3) Rapid quenching: After the reactants leave the high-temperature zone, they are rapidly cooled, which suppresses phase separation and segregation in the multi-component system, achieves uniform mixing of each metal element at the atomic level, and finally forms a high-entropy oxide with a single-phase crystal structure.

[0028] In this embodiment, spinel high-entropy oxide materials are prepared using this method. Compared with existing synthesis methods, the preparation method provided by this invention has at least the following advantages: 1) Simple process and short cycle: This invention only requires two steps: preparation of multi-metal salt precursor and plasma reaction. The plasma reaction time is only a few minutes (3min-8min). Compared with the traditional solid-state reaction calcination process that takes several hours to tens of hours, the synthesis cycle is greatly shortened and the preparation efficiency is improved.

[0029] 2) Achieve atomic-level uniform mixing and rapid conversion in one step: This invention utilizes the high temperature and high activity characteristics of inductively coupled plasma jets to rapidly decompose and oxidize mixed polymetallic salt precursors within minutes to form a single spinel phase high-entropy oxide, eliminating the need for subsequent high-temperature annealing and avoiding the element segregation problem caused by long-term high-temperature sintering in traditional methods.

[0030] 3) High conversion efficiency: Through actual weighing and theoretical calculation, the metal elements in the preparation method provided by this invention are basically completely converted, the raw material utilization rate is high, and it conforms to the green and efficient preparation concept.

[0031] 4) Wide range of applications: The method of this invention can be flexibly extended to the synthesis of other multi-component high-entropy oxide systems by adjusting the type and ratio of precursor metal salts, and has good universality.

[0032] In some embodiments, the iron salt is selected from, but is not limited to, one or more of ferric nitrate, ferric chloride, ferric sulfate, and ferric acetate; the cobalt salt is selected from, but is not limited to, one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate; the nickel salt is selected from, but is not limited to, one or more of nickel nitrate, nickel chloride, nickel sulfate, and nickel acetate; the manganese salt is selected from, but is not limited to, one or more of manganese nitrate, manganese chloride, manganese sulfate, and manganese acetate; and the copper salt is selected from, but is not limited to, one or more of copper nitrate, copper chloride, copper sulfate, and copper acetate. Selecting the above-mentioned iron, cobalt, nickel, manganese, and copper salts provides a stable and widely available source of metal cations for the system, ensuring that the five metal elements are uniformly introduced into the polymetallic salt precursor according to the designed proportions.

[0033] In a preferred embodiment, the iron salt is ferric nitrate (Fe(NO3)3·9H2O); the cobalt salt is cobalt nitrate (Co(NO3)2·6H2O); the nickel salt is nickel nitrate (Ni(NO3)2·6H2O); the manganese salt is manganese nitrate (Mn(NO3)2·4H2O); and the copper salt is copper nitrate (Cu(NO3)2·3H2O).

[0034] In some embodiments, the metal elements in the iron salt, cobalt salt, nickel salt, manganese salt, and copper salt are in equimolar ratios. Controlling the molar ratio of the metal elements in the five metal salts to an equimolar ratio facilitates highly uniform mixing and random distribution of the five metal ions at the atomic scale, minimizing segregation tendencies caused by differences in element content, promoting the formation of a single, homogeneous, high-entropy solid solution structure, avoiding the formation of impurity phases or independent metal oxide phases, and ensuring the phase purity and structural stability of the material. Simultaneously, the equal molar content of the five metal elements can fully utilize the inherent characteristics of high-entropy effects, such as lattice distortion, diffusion retardation, and the cocktail effect, resulting in moderate lattice distortion, increasing internal defects and active sites in the material, and simultaneously improving the thermodynamic stability and structural resilience of the system. Furthermore, equimolar composition can balance the electrochemical, catalytic, or magnetic properties of iron, cobalt, nickel, manganese, and copper, achieving synergistic enhancement of the functions of multiple elements. This avoids excessive dominance of metal elements, which weakens the overall performance. As a result, the spinel high-entropy oxide material produced exhibits better performance in terms of ion conduction, redox activity, specific capacity, and cycle stability, making it more conducive to obtaining repeatable and controllable spinel high-entropy oxide materials.

[0035] In some embodiments, the stirring treatment time is 0.5h-2h; the ultrasonic treatment time is 0.5h-2h; and the freeze-drying treatment time is 24h-48h.

[0036] In this embodiment, iron, cobalt, nickel, manganese, and copper salts are mixed with a solvent and stirred for 0.5-2 hours. This process allows the five metal salts to initially dissolve in the solvent and achieve macroscopically uniform mixing, preventing excessively high local metal ion concentrations or the appearance of undissolved salt particles, thus laying the foundation for subsequent uniform dispersion. Following the stirring process, ultrasonic treatment for 0.5-2 hours further breaks up metal ion aggregates through microscopic disturbances generated by cavitation, promoting uniform dispersion of metal ions at the molecular or ionic scale and significantly improving the homogeneity of the mixed solution. Finally, the mixed solution is freeze-dried for 24-48 hours. This allows the solvent to rapidly sublimate and dehydrate under low-temperature vacuum conditions, avoiding solute migration, segregation, and particle agglomeration caused by traditional heating and drying. It also preserves the loose and porous microstructure, ensuring a highly uniform distribution of the five metal elements. Ultimately, a multi-metallic salt precursor with a loose structure, uniform composition, and large specific surface area is obtained, providing a good structural basis for the subsequent formation of pure-phase, highly crystalline, and stable spinel high-entropy oxides through plasma reaction.

[0037] In a preferred embodiment, the stirring treatment lasts for 1 hour; the ultrasonic treatment lasts for 1 hour; and the freeze-drying treatment lasts for 24 hours.

[0038] In some embodiments, the distance between the plasma torch inlet of the inductively coupled plasma reactor and the polymetallic salt precursor is 5mm-20mm. Controlling the distance between the plasma torch inlet and the polymetallic salt precursor within this range allows the plasma to simultaneously undergo three key processes—instantaneous pyrolysis oxidation, synchronous dehydration, and rapid quenching—within milliseconds when acting on the polymetallic salt precursor, thereby achieving the preparation of high-entropy oxide materials with various single-phase crystal structures.

[0039] In a preferred embodiment, the distance between the plasma torch inlet of the inductively coupled plasma reactor and the polymetallic salt precursor is 8mm-12mm.

[0040] Specifically, in step S30, the multi-metal salt precursor is placed in the groove of a quartz vessel, and then the quartz vessel containing the multi-metal salt precursor is placed on the sample platform of the inductively coupled plasma reactor (ICP-RT). The distance between the upper surface of the quartz vessel and the plasma torch inlet of the ICP-RT is adjusted to 5mm-20mm. Preferably, the distance between the upper surface of the quartz vessel and the plasma torch inlet of the ICP-RT is 8mm-12mm.

[0041] In some embodiments, the plasma reaction power is 500W-1000W and the plasma reaction time is 3min-8min. Controlling the plasma reaction power and time within the above range can rapidly increase the temperature field of the polymetallic salt precursor, thereby rapidly converting the polymetallic salt precursor into spinel high-entropy oxide material.

[0042] In a preferred embodiment, the plasma reaction power is 650W-800W, and the plasma reaction time is 4min-6min. More preferably, the plasma reaction power is 700W, and the plasma reaction time is 5min.

[0043] In some embodiments, the surface temperature of the polymetallic salt precursor is 800℃-1200℃ during the plasma reaction. Within this range, the high-temperature field attracts a large number of active oxygen species (such as oxygen atoms and excited-state oxygen molecules), causing the metal salt to decompose and oxidize rapidly. Simultaneously, adsorbed water and water of crystallization in the polymetallic salt precursor are vaporized instantaneously, promoting heat transfer and reaction uniformity. Furthermore, the reactants are rapidly cooled after the plasma reaction, suppressing phase separation and segregation in the multi-component system and achieving uniform mixing of the metal elements at the atomic level.

[0044] In some embodiments, the working gas for the plasma reaction is a mixture of argon and oxygen; the flow rate of the argon is 1.0 slm-2.0 slm, and the flow rate of the oxygen is 30 sccm-100 sccm; using the mixture of oxygen and argon as the ignition gas, a high-temperature plasma jet containing highly active particles can be generated through inductive coupling between a high-frequency electromagnetic field and oxygen and argon, thereby enabling the polymetallic salt precursor to undergo instantaneous pyrolysis oxidation, synchronous dehydration, and rapid quenching within milliseconds, ultimately forming a high-entropy oxide material with a single-phase crystal structure.

[0045] In a preferred embodiment, the working gas for the plasma reaction is a mixture of argon and oxygen; the flow rate of the argon is 1.5 slm, and the flow rate of the oxygen is 60 sccm.

[0046] In some embodiments, the cooling process involves introducing a cooling gas. Preferably, the cooling gas is argon, and the flow rate is 15 slm-25 slm. More preferably, the flow rate is 18 slm. Using a cooling gas to cool the products after the plasma reaction allows for rapid quenching, achieving a sharp cooling effect, thereby suppressing phase separation and segregation in multi-component systems and achieving uniform mixing of the various metal elements at the atomic level.

[0047] In some embodiments, after the plasma reaction is complete, the quartz vessel is removed from the sample stage, and the product is rapidly cooled to obtain uniform nanoparticle-shaped high-entropy metal oxides.

[0048] In some embodiments, the solvent is, but is not limited to, at least one of deionized water and anhydrous ethanol.

[0049] In addition, the present invention also provides a spinel high-entropy oxide material, which is prepared by the preparation method of the spinel high-entropy oxide material.

[0050] In this embodiment, only two steps are required: preparation of the polymetallic salt precursor and plasma reaction. The plasma reaction time is only a few minutes (3-8 minutes), which significantly shortens the synthesis cycle and improves the preparation efficiency compared to the traditional solid-state reaction calcination process that takes several hours to tens of hours. Furthermore, by utilizing the high temperature and high activity characteristics of the inductively coupled plasma jet, the mixed polymetallic salt precursor is rapidly decomposed and oxidized within minutes to form a single spinel phase high-entropy oxide, eliminating the need for subsequent high-temperature annealing and avoiding the elemental segregation problem caused by prolonged high-temperature sintering in traditional methods. This method can achieve the preparation of high-entropy oxides with atomic-level uniform mixing of multiple metals, controllable product microstructure, simple process, low energy consumption, and scale-up potential.

[0051] In some embodiments, the particle size of the spinel high-entropy oxide material is 200nm-450nm.

[0052] In addition, the present invention also provides an application of spinel high-entropy oxide material in water electrolysis catalyst.

[0053] In this embodiment, the spinel high-entropy oxide material is applied to the water electrolysis catalyst, exhibiting good OER performance.

[0054] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention.

[0055] Example 1 This embodiment provides a spinel high-entropy oxide material, the preparation steps of which specifically include: Weigh out 1.028g Fe(NO3)3·9H2O, 0.74g Co(NO3)2·6H2O, 0.74g Ni(NO3)2·6H2O, 0.638g Mn(NO3)2·4H2O, and 0.614g Cu(NO3)2·3H2O, dissolve them in deionized water, and then perform magnetic stirring for 1 h, ultrasonic treatment for 1 h, and freeze-drying for 24 h to obtain a polymetallic salt precursor. 0.5 g of the polymetallic salt precursor was placed in the groove of a quartz vessel, and the quartz vessel containing the polymetallic salt precursor was placed on the sample stage of an inductively coupled plasma reactor. The upper surface of the quartz vessel was 10 mm from the torch nozzle. The ignition argon flow rate was 1.5 slm, the oxygen flow rate was 60 sccm, the cooling argon flow rate was 18.0 slm, the surface temperature of the polymetallic salt precursor was about 1200℃, the reaction was carried out for 5 min, and then the vessel was removed and cooled to obtain a spinel high-entropy oxide material with the chemical formula (MnFeCoNiCu)3O4.

[0056] The spinel high-entropy oxide material prepared in this embodiment was characterized, and its X-ray diffraction pattern is shown below. Figure 2 As shown, the positions of its diffraction peaks are similar to those of the standard spinel oxide CoCuMnO. x(PDF # 47-0324) shows a high degree of agreement, with no identifiable impurity phase diffraction peaks found, indicating that the prepared sample successfully formed a spinel structure M3O4 (M represents metal). Specifically, the main diffraction peaks of (MnFeCoNiCu)3O4 appear at 19.1°, 31.0°, 36.4°, 38.0°, 44.1°, 54.5°, 58.1° and 63.7°, respectively, which precisely correspond to the (111), (220), (311), (222), (400), (422), (511) and (440) crystal planes of the spinel structure, confirming the uniform solid solution of multiple metal ions in the lattice and the integrity of the crystal structure.

[0057] The TEM results of the spinel high-entropy oxide material prepared in this embodiment are shown in the figure below. Figure 3 As shown, where Figure 3 Images (a) and (b) are transmission electron microscope (TEM) images at different magnifications, (c) is a high-magnification TEM image, and (d) is the selected area electron diffraction (SED) pattern. The TEM images show that (MnFeCoNiCu)3O4 exhibits a nanosheet morphology. The high-magnification TEM image reveals the crystal plane exposure of (MnFeCoNiCu)3O4; clearly, (MnFeCoNiCu)3O4 has distinct 0.29 nm lattice fringes, which are attributed to CoCuMnO. x The (022) crystal plane indicates excellent crystallinity of the material. Selective electron diffraction analysis was used to further characterize the crystal plane exposure of (MnFeCoNiCu)3O4, such as... Figure 3 As shown in (d), SAED reveals two distinct diffraction rings, corresponding to CoCuMnO and CoCuMnO, respectively. x The (022) and (124) crystal planes of (Standard Card PDF # 47-0324) are consistent with the HRTEM and XRD results, further confirming that the product has a spinel structure.

[0058] In addition, the TEM-EDS elemental surface distribution map is as follows: Figure 4 As shown, where, Figure 4 In the diagram, (a) represents the selected region, (b) represents Mn, (c) represents Fe, (d) represents Co, (e) represents Ni, (f) represents Cu, and (g) represents O; Figure 4It can be seen that Mn, Fe, Co, Ni, Cu, and O elements are uniformly distributed in the sample, with no obvious element enrichment or separation. The atomic ratio of each element was determined by ICP-MS. The atomic ratio calculated based on the concentration data is Mn:Fe:Co:Ni:Cu = 5.18:4.95:5.33:5.21:5.53. The atomic percentage of each metal element is close to the ideal 1:1:1:1:1, confirming that Mn, Fe, Co, Ni, and Cu have achieved uniform solid solution at the atomic scale in the material lattice, further verifying the high-entropy oxide characteristics of the product.

[0059] The spinel high-entropy oxide material (MnFeCoNiCu)3O4 prepared in this embodiment was used as a catalyst in the field of water electrolysis. The oxygen evolution reaction performance of the catalyst was tested using a three-electrode system, as detailed below: A saturated calomel electrode was used as the reference electrode, a platinum electrode as the counter electrode, and a catalyst-supported carbon paper electrode as the working electrode. The electrolyte was a 1 mol / L KOH solution, the test temperature was 25°C, and the instrument was a Metrohm Autolab electrochemical workstation. Overpotential, Tafel slope, double-layer capacitance, and electrochemical active area were obtained by linear sweep voltammetry and cyclic voltammetry, respectively.

[0060] The working electrode was prepared as follows: 3 mg of catalyst ((MnFeCoNiCu)3O4) and 1 mg of carbon black were dispersed in 497 μL of anhydrous ethanol and 3 μL of Nafion solution, and the mixture was sonicated for 30 min to obtain a slurry; the carbon paper was treated with an oxygen plasma cleaner on both sides for 3 min each to enhance its hydrophilicity; 10 μL of the slurry was uniformly coated on one side of the carbon paper (coating area 1×1 cm). 2 The catalyst loading was 3 mg / cm³. 2 Infrared drying or natural air drying.

[0061] The electrochemical performance characterization diagram of the catalyst using the above method is shown below. Figure 5 As shown, where, Figure 5 In the diagram, (a) represents the linear sweep voltammetry method, (b) represents the Tafel slope, (c) represents the double-layer capacitance, and (d) represents the cyclic voltammetry method. Figure 5 In (a), the overpotential can be calculated and the Tafel slope can be obtained by fitting; from Figure 5 The double-layer capacitance can be calculated from (d) in the figure, and then the electrochemical active area can be calculated; it can be seen that the catalyst is at 10 mA / cm². 2 The overpotential at the current density is 347 mV, the Tafel slope is 201.8 mV / dec, and the double-layer capacitance is 36.51 mF / cm². 2 The electrochemical active area reaches 912.75 cm². 2 .

[0062] Example 2 This embodiment provides a spinel high-entropy oxide material, the preparation steps of which specifically include: Weigh out 1.028g Fe(NO3)3·9H2O, 0.74g Co(NO3)2·6H2O, 0.74g Ni(NO3)2·6H2O, 0.638g Mn(NO3)2·4H2O, and 0.614g Cu(NO3)2·3H2O, dissolve them in deionized water, and then perform magnetic stirring for 1.5 h, ultrasonic treatment for 1.5 h, and freeze-drying for 30 h to obtain a polymetallic salt precursor. 0.5 g of polymetallic salt precursor was placed in the groove of a quartz vessel, and the quartz vessel containing the polymetallic salt precursor was placed on the sample stage of an inductively coupled plasma reactor. The upper surface of the quartz vessel was 5 mm from the torch nozzle. The ignition argon flow rate was 1.5 slm, the oxygen flow rate was 60 sccm, the cooling argon flow rate was 18.0 slm, the surface temperature of the polymetallic salt precursor was about 1200℃, the reaction was carried out for 3 min, and then the vessel was removed and cooled to obtain a spinel high-entropy oxide material with the chemical formula (MnFeCoNiCu)3O4.

[0063] Example 3 This embodiment provides a spinel high-entropy oxide material, the preparation steps of which specifically include: Weigh out 1.028g Fe(NO3)3·9H2O, 0.74g Co(NO3)2·6H2O, 0.74g Ni(NO3)2·6H2O, 0.638g Mn(NO3)2·4H2O, and 0.614g Cu(NO3)2·3H2O, dissolve them in deionized water, and then perform magnetic stirring for 1 h, ultrasonic treatment for 1 h, and freeze-drying for 24 h to obtain a polymetallic salt precursor. 0.5 g of the polymetallic salt precursor was placed in the groove of a quartz vessel, and the quartz vessel containing the polymetallic salt precursor was placed on the sample stage of an inductively coupled plasma reactor. The upper surface of the quartz vessel was 12 mm from the torch nozzle, the ignition argon flow rate was 1.5 slm, the oxygen flow rate was 80 sccm, the cooling argon flow rate was 18.0 slm, the surface temperature of the polymetallic salt precursor was about 1200℃, the reaction was carried out for 3 min, and then the vessel was removed and cooled to obtain a spinel high-entropy oxide material with the chemical formula (MnFeCoNiCu)3O4.

[0064] In summary, this invention provides a spinel high-entropy oxide material, its preparation method, and its application. The preparation method of the spinel high-entropy oxide material includes the following steps: mixing iron salt, cobalt salt, nickel salt, manganese salt, and copper salt with a solvent, followed by stirring and ultrasonic treatment to obtain a mixed solution; freeze-drying the mixed solution to obtain a multi-metal salt precursor; and placing the multi-metal salt precursor in an inductively coupled plasma reactor (ICP-RT) device, followed by plasma reaction and cooling to obtain the spinel high-entropy oxide material. This invention utilizes a solution mixing method to sequentially stir, ultrasonically treat, and freeze-dry iron salt, cobalt salt, nickel salt, manganese salt, and copper salt in a solvent environment to obtain a multi-metal salt precursor. Then, using an ICP-RT device, a high-temperature plasma jet containing highly active particles is generated through inductive coupling between a high-frequency electromagnetic field and a working gas. When the plasma acts on the multi-metal salt precursor, it simultaneously undergoes instantaneous pyrolysis oxidation, synchronous dehydration, and rapid quenching within milliseconds, thereby achieving uniform mixing of the various metal elements at the atomic level, ultimately forming a high-entropy oxide with a single-phase crystal structure. Meanwhile, this method can be used to prepare high-entropy oxides with atomic-level uniform mixing of multiple metals, controllable product microstructure, simple process, low energy consumption, and scale-up potential.

[0065] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing a spinel high-entropy oxide material, characterized in that, Including the following steps: Iron salts, cobalt salts, nickel salts, manganese salts, and copper salts are mixed with a solvent, and then subjected to stirring and ultrasonic treatment to obtain a mixed solution. The mixed solution was freeze-dried to obtain a multi-metal salt precursor; The polymetallic salt precursor was placed in an inductively coupled plasma reactor and cooled after plasma reaction to obtain spinel high-entropy oxide material.

2. The method for preparing spinel high-entropy oxide material according to claim 1, characterized in that, The iron salt is selected from one or more of ferric nitrate, ferric chloride, ferric sulfate, and ferric acetate; the cobalt salt is selected from one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate; the nickel salt is selected from one or more of nickel nitrate, nickel chloride, nickel sulfate, and nickel acetate; the manganese salt is selected from one or more of manganese nitrate, manganese chloride, manganese sulfate, and manganese acetate; and the copper salt is selected from one or more of copper nitrate, copper chloride, copper sulfate, and copper acetate.

3. The method for preparing spinel high-entropy oxide material according to claim 1, characterized in that, The iron salt, cobalt salt, nickel salt, manganese salt, and copper salt contain metal elements in equal molar ratios.

4. The method for preparing spinel high-entropy oxide material according to claim 1, characterized in that, The stirring treatment time is 0.5h-2h; the ultrasonic treatment time is 0.5h-2h; and the freeze-drying treatment time is 24h-48h.

5. The method for preparing spinel high-entropy oxide material according to claim 1, characterized in that, The distance between the plasma torch inlet of the inductively coupled plasma reactor and the polymetallic salt precursor is 5mm-12mm.

6. The method for preparing spinel high-entropy oxide material according to claim 1, characterized in that, The plasma reaction has a power of 500W-1000W and a reaction time of 3min-8min. Preferably, during the plasma reaction, the surface temperature of the polymetallic salt precursor is 800℃-1200℃.

7. The method for preparing spinel high-entropy oxide material according to claim 1, characterized in that, The working gas for the plasma reaction is a mixture of argon and oxygen; the flow rate of the argon is 1.0 slm-2.0 slm, and the flow rate of the oxygen is 30 sccm-100 sccm. Preferably, the cooling process involves introducing cooling gas.

8. A spinel high-entropy oxide material, characterized in that, It is prepared using the spinel high-entropy oxide material preparation method according to any one of claims 1-7.

9. The spinel high-entropy oxide material according to claim 8, characterized in that, The spinel high-entropy oxide material has a particle size of 200nm-450nm.

10. The application of a spinel high-entropy oxide material as described in any one of claims 8-9 in a water electrolysis catalyst.